2022
DOI: 10.3389/fenvs.2022.983136
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: G-20 economies and their environmental commitments: Fresh analysis based on energy consumption and economic growth

Abstract: The impact of economic growth and energy use is still controversial regarding sustainability, and researchers have limited consensus in this regard. Electricity is considered more environmentally friendly compared with direct fossil fuel consumption. However, many developed economies still depend on fossil fuel sources for electricity generation. Therefore, this study attempted to verify the relationship between electricity consumption and carbon emissions in developed economies in the Group of Twenty (G20). E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The authors of [51] also showed that increasing the consumption of REC reduces CO 2 emissions through the development and implementation of technologies that are energy-efficient and environmentally friendly. The relationship between REC, GDP, FDI, TO and CO 2 emissions in the G20 countries was investigated in [52]. This study showed that GDP and FDI had a significant positive effect on CO 2 emissions, which confirms the "Pollution Heaven Hypothesis".…”
Section: Moments Quantile Regressionmentioning
confidence: 54%
“…The authors of [51] also showed that increasing the consumption of REC reduces CO 2 emissions through the development and implementation of technologies that are energy-efficient and environmentally friendly. The relationship between REC, GDP, FDI, TO and CO 2 emissions in the G20 countries was investigated in [52]. This study showed that GDP and FDI had a significant positive effect on CO 2 emissions, which confirms the "Pollution Heaven Hypothesis".…”
Section: Moments Quantile Regressionmentioning
confidence: 54%
“…The analysis revealed a positive correlation between economic growth and energy consumption in several countries, leading to increased CO2 emissions. Li et al [29] conducted research in the G20 countries, employing several econometric techniques such as cross-sectional dependence, cointegration, FMOLS, DOLS, and the pair-wise panel Granger causality test. This analysis reveals a long-term elasticity that demonstrates a notable positive impact of both renewable and non-renewable energy consumption on economic activity within various sectors and overall economic output.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The energy cleanability gap, however, substantially impacts several unstudied socioeconomic aspects. Moreover, existing literature covers mainly developed countries' sustainability perspective, i.e., Akhtar, M. J., Ashraf, W., Rehman, H. (2020); Li et al, (2022); Akhter, M. J., Rehman, H., & Abass, Q. (2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the 10th to 40th quantiles, where DEX has a substantial impact, contradict former GMM results. In this regard, P Li et al (2022). concluded that development spending is a big booster for economic sustainability.…”
mentioning
confidence: 99%